POLA PEMALSUAN SANAD DALAM PERIWAYATAN HADIS: Pandangan Muhaddiś˚n dan Orientalis - Arif Chasanul Muna (JURNAL PENELITIAN, 2012)
This study aimed to address three issues: [1] how the orientalists think of forgery pattern of sanad in hadith transmission; [2] how the muhaddiśūn think of forgery pattern of sanad in hadith transmission; and [3] what the similarities and differences are between the views of the orientalists and muhaddiśūn on forgery pattern of sanad. The results of this study indicate that in general the view of the muhaddiśūn and orientalists on the counterfeiting of sanad are very fundamental difference. Although the forgery patterns of sanad identified by the muhaddiśūn and orientalist are similar, their views are very different. It is because the orientalist approach is skeptic that does not recognize the existence of the original matan sourced from the Prophet Pbuh, so that it gives a major influence on the different methods used by orientalists and muhaddiśūn to analyze hadith, especially the isnaad aspect.